Manajemen Keuangan dalam Kesejahteraan Keluarga Petani di Desa Bener Kecamatan Wonosari Kabupaten Klaten - Indah Sukmawati; Risda Rizkillah; Swastiko Priyambodo; Bonjok Istiaji (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
This study aims to analyze the management of farm family and its relation to the well-being of farm family in Bener Village, Klaten Regency, Central Java Province. This study involved two families selected from the head of a farmer group in the village. Data collection is done through observation and in-depth interviews using questionnaires. Well-being is measured by how well the family is able to meet economic indicators, health, education, social resources and life satisfaction. The results showed that there was a relationship between family financial management and family welfare which was also influenced by respondents' income. Keyword : economic, family, farmer, financial management, welfare